HUKUM DAN KEADILAN DALAM PERSFEKTIF FILSAFAT HUKUM - Edward L. Panjaitan (Fakultas Hukum Universitas Kristen Indonesia, 2018)
Abstract Talking about law is about human relations. Talking about human relationships is about justice. Thus, any dis- cussion about the law, clear or vague, is always a discussion about justice too. We cannot talk about the law only to its form as a formal relationship. We also need to see it as an expression of the ideals of justice of the people. The nature of justice is in the eld of philosophy, therefore the problem of justice was initiated by philosophers from time immemorial. Keyword : human relations; justice; the ideals of justice .